Global banks on trial : U.S. prosecutions and the remaking of international finance - Verdier, Pierre-Hugues (New York : Oxford University Press, 2020)
The book provides a concise, readable, and up-to-date explanation of the numerous criminal prosecutions and large fines imposed on global banks for market manipulation, tax evasion, sanctions evasion, and money laundering. The book connects these cases with broader debates: Are global banks "too big to jail"? How much control can states exercise over global finance? Can they succeed in fighting problems such as market manipulation or tax evasion? Is U.S. unilateralism in this area to be feared, or does it pave the way for beneficial global reforms?
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 30, 2020).
Keywords: Banking law -- United States -- Criminal provisions; Banks and banking, International -- Law and legislation -- United States -- Criminal provisions; Criminal jurisdiction -- United States; Law; Laws of specific jurisdictions & specific areas of law